Étienne Balibar, La igualibertad - Cueva Fernández, Ricardo (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
Este artículo reseña: Étienne Balibar, La igualibertad. Barcelona. Herder, 2017, 496 pp.